Pentingnya Pelajaran Aqidah Islam dalam Membentuk Kepribadian Siswa - Shelin Patrisia; Shellanda Monica; Tiara Nurhayati (STAI AL-AMIN, 2025)
Islamic creed education at Madrasah Ibtidaiyah is essential in forming students' personality. Its importance has grown in today's challenging era due to the increasing influence of foreign cultures that conflict with Islamic values. The purpose of this research is to investigate how much Islamic creed instruction influences the character development of MI Darussalam Pagaralam students.